Identification of factors of vulnerability of self-employed workers and in relation to dependency in times of COVID-19 in Ecuador - Caiza, Josselyn (2021)
The measures taken by governments to stop the spread of COVID-19 helped reduce infections, however, they paralyzed several economic sectors. This implied a slowdown in production, which was reflected in layoffs and a reduction in working hours, which translated into a reduction in labor income. This research work seeks to determine the characteristics of the workers who have been most vulnerable to the COVID-19 crisis. For this study, the data from the "Survey to evaluate the effect of the health crisis on workers" carried out by the Departments of Quantitative Economics and Mathematics of the National Polytechnic School are used. Different levels of impact are analyzed through the quantification of income reduction, therefore, a Generalized Ordered Logit model is estimated. The results show that workers who totally paralyzed their activities, workers who belonged to an income stratum between $ 0 and $ 500 per month, self-employed workers, workers who do not have health insurance, those workers who have debts and who do not owning savings are more likely to experience a greater impact on their income.